Damage mode identification and classification using smart piezoceramic transducer - Lu, Leon Sunjie. (2009)
This project investigated the feasibility of adopting smart piezoceramics, particularly Lead Zirconate Titanate (PZT) patches, in identifying the type and nature of damage in terms of mechanical impedance. Electro-mechanical impedance (EMI) technique employing PZT, which aims to predict structure’s health, were conducted experimentally. Explanations were presented to describe modal frequencies and peak magnitudes.